2021
DOI: 10.32481/djph.2021.12.014
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Seasonal Trends in Delaware Drug Overdoses, 2016-2020

Abstract: Objective: To examine whether overdose deaths and related metrics-overdose calls for service to police and non-fatal overdose emergency department visits-in Delaware follow within-year (i.e., seasonal) patterns during the most recent years of the opioid epidemic (2016)(2017)(2018)(2019)(2020). Methods: We begin by providing descriptive statistics on yearly trends in overdose metrics, followed by Analysis of Variance (ANOVA) to analyze whether seasonal variations have a significant impact on the patterns of Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our discovery of a seasonal trend in the overdose case fatality rate, where the proportion of deaths from drug overdoses is higher in the winter than in the summer, is a novel finding. Previous studies have identified seasonal trends in various drug surveillance data sources in the past decade, some with conflicting results (Abraham et al, 2021). For example, Sadler and Furr‐Holden (2019) reported the highest counts of fatal drug overdoses in spring months and lowest counts of fatal drug overdoses in summer months in Michigan from 2013 to 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Our discovery of a seasonal trend in the overdose case fatality rate, where the proportion of deaths from drug overdoses is higher in the winter than in the summer, is a novel finding. Previous studies have identified seasonal trends in various drug surveillance data sources in the past decade, some with conflicting results (Abraham et al, 2021). For example, Sadler and Furr‐Holden (2019) reported the highest counts of fatal drug overdoses in spring months and lowest counts of fatal drug overdoses in summer months in Michigan from 2013 to 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The number of consumptions and visits in July of 2023 was 224 and 153 respectively and there was 241 consumptions and 201 visits in August of 2023. Research suggests that there may be seasonal impacts on substance use as drug initiation, overdose emergency room visits,police calls for overdoses, and overdoses themselves usually tend to spike in the summer months [ 16 , 17 ]. In terms of new clients, it appears that this number peaked in December 2022, and has remained relatively consistent within the last five months, with a small reduction in May 2023.…”
Section: Discussionmentioning
confidence: 99%